USE OF SILASTIC AS INTERPOSITIONAL MATERIAL IN THE MANAGEMENT OF UNILATERAL TEMPOROMANDIBULAR JOINT ANKYLOSIS - Akhtar, Muhammad Usman; Abbas, Iram; Shah, Adnan Ali (Journal of Ayub Medical College Abbottabad, 2006)
Background: Ankylosis is a very common condition developed mainly after damage to mandibular condyles or temporomandibular joint (TMJ) at a growing age. Different autogenous and alloplastic interpositional materials have been attempted after the resection of the ankylotic bone to achieve desirable results. This condition is relatively common in Pakistan. We treated TMJ ankylosis with alloplastic medical grade silicone silastic interpositional arthroplasty. Eight joints accompanied ipsilateral or contralateral coronoidectomy to achieve desirable results. Method: All patients were presented at Punjab Dental Hospital Lahore. Sixty-one joints with unilateral TMJ ankylosis were underwent surgery after careful examination and final radiographic confirmation. The preoperative CT scan was also performed in few patients. Results: The postoperative measurements of the interincisal opening with lateral and protrusive jaw movements were criteria for success of surgery. The lateral and protrusive jaw movements were assessed as excellent, good and poor. Less than 25 mm interincisal opening was considered as poor jaw opening. Conclusion: The overall success rate was 98.4 % with 84 % desirable interincisal jaw opening. Less than 5 % patients were observed with poor jaw opening. The immediate late complications were transient and were included oedema, weakness of a branch of the facial nerve on the operated side. Two implants were infected along with one wire in the first month of surgery and were removed under local anaesthesia without further complication. Key words: Ankylosis, silastic, interpositional material, arthroplasty, coronoidectomy and jaw movements.